2021
DOI: 10.3390/molecules26061568
|View full text |Cite
|
Sign up to set email alerts
|

[89Zr]-Pertuzumab PET Imaging Reveals Paclitaxel Treatment Efficacy Is Positively Correlated with HER2 Expression in Human Breast Cancer Xenograft Mouse Models

Abstract: Paclitaxel (PTX) treatment efficacy varies in breast cancer, yet the underlying mechanism for variable response remains unclear. This study evaluates whether human epidermal growth factor receptor 2 (HER2) expression level utilizing advanced molecular positron emission tomography (PET) imaging is correlated with PTX treatment efficacy in preclinical mouse models of HER2+ breast cancer. HER2 positive (BT474, MDA-MB-361), or HER2 negative (MDA-MB-231) breast cancer cells were subcutaneously injected into athymic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Molecular imaging has been utilized to evaluate changes in HER2+ breast cancer to predict eventual response [ 18 , 19 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Whisenant et al used [ 18 F]-FLT-PET imaging to monitor trastuzumab therapeutic response in tumor proliferation in trastuzumab-sensitive and -resistant models and found that [ 18 F]-FLT-PET imaging could be used to inform longitudinal trastuzumab sensitivity as early as 24 h after the first therapeutic dose [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular imaging has been utilized to evaluate changes in HER2+ breast cancer to predict eventual response [ 18 , 19 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Whisenant et al used [ 18 F]-FLT-PET imaging to monitor trastuzumab therapeutic response in tumor proliferation in trastuzumab-sensitive and -resistant models and found that [ 18 F]-FLT-PET imaging could be used to inform longitudinal trastuzumab sensitivity as early as 24 h after the first therapeutic dose [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intratumoral heterogeneity is known to influence tumor progression and introduces a significant challenge in the clinical treatment of HER2+ breast cancer, as diagnostically similar patients may respond differently to the same treatment strategy [ 7 , 8 , 9 ]. Previous efforts have demonstrated that heterogeneous HER2 expression exists within HER2+ tumors [ 10 , 11 , 12 ] and shown that HER2+ status alone does not necessarily correlate with objective response to HER2-targeted treatment [ 6 , 8 , 9 , 11 ]. The ability to quantitatively characterize intratumoral heterogeneity and its changes in response to therapy may provide clinically valuable information that can be used to guide treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Atezolizumab was conjugated to DFO-Bz-NCS and labeled with [ 89 Zr]oxalate according to previously reported methods [23][24][25]. Briefly, 2, 5, 10, and 20-fold molar excess of DFO-Bz-NCS (8 mg/mL, diluted in DMSO) was conjugated to atezolizumab (1 mg; 17 µL) in 0.1 M sodium carbonate buffer pH 9 (q.s.…”
Section: Synthesis Of [ 89 Zr]-atezolizumabmentioning
confidence: 99%